Systematic Literature Review and Meta-Analysis of Response to First-Line Therapies for Advanced/Metastatic Urothelial Cancer Patients Who Are Cisplatin Ineligible - Freshwater, Tomoko; Li, Haojie; Valiathan, Chandni; Li, Mengyao; Perini, Rodolfo; Bracco, Oswaldo L; Frenkl, Tara; Keefe, Stephen (American journal of clinical oncology, 2019)
The purpose of this systematic literature review (SLR) and meta-analysis was to compile the response of historic treatment options in first-line settings for patient populations who are cisplatin ineligible. SLR was conducted to compile objective response rate (ORR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS) of historic therapies for this population based on stringent criteria. Clinical trials published in English from January 1991 to June 2016 were identified by searching the PubMed (Medline), Cochrane, and Embase databases. Eighteen studies (21 arms; N=810) were identified and used for this meta-analysis. For all treatments included in these studies, the pooled ORR was 0.36 (95% confidence interval [CI], 0.30-0.42). The ORR for the carboplatin+gemcitabine arms (6 arms; N=259), which is the National Comprehensive Cancer Network's recommended first-line treatment (before approval of atezolizumab and pembrolizumab) for this population was 0.36 (95% CI, 0.30-0.42), the median DOR (4 arms) was 7.00 months (95% CI, 4.34-11.29), and the median OS was 8.39 months (95% CI, 7.05-9.98). The results of this SLR clearly demonstrate the paucity of clinical studies that assess therapeutic intervention in truly cisplatin-ineligible advanced/metastatic urothelial carcinoma subjects and highlight the development of novel therapies that can create real improvement in long-term outcomes. The recent approval of 2 checkpoint inhibitors, atezolizumab and pembrolizumab, were added in the National Comprehensive Cancer Network guidance as recommended first-line treatment for cisplatin-ineligible patients with advanced/metastatic urothelial carcinoma and has provided alternatives for this patient population.